Sex Differences in the Neuroadaptations of Reward-related Circuits in Response to Subchronic Variable Stress. (15th April 2018) - Zhang, Song; Zhang, Hongxing; Ku, Stacy M.; Juarez, Barbara; Morel, Carole; Tzavaras, Nikos; Montgomery, Sarah; Hodes, Georgia E.; Brancato, Anna; Russo, Scott J.; Cao, Jun-Li; Han, Ming-Hu
Highlights: We replicated that SCVS induced a depressed susceptible phenotype in female but not male mice. The firing activity of LHb-VTA circuit neurons was dramatically increased selectively in female mice that underwent SCVS. VTA dopamine neurons and LC-VTA circuit did not display firing differences between stressed and control mice in both sexes. Abstract: Women are twice as likely to be diagnosed with major depressive disorder. However, fewer studies in rodent models of depression have used female animals, leading to a relative lack of understanding of the female brain's response to stress, especially at a neural circuit level. In this study, we utilized a 6-day subchronic variable stress (SCVS) mouse model and measured novelty suppressed feeding as behavioral criteria to evaluate susceptibility to SCVS in male and female mice. First, we showed that SCVS induced a decrease in latency to eat (susceptible phenotype) in female mice, but not in males (resilient phenotype). After determining behavioral phenotypes, we investigated the firing activities of dopamine (DA) neurons in the ventral tegmental area (VTA), as well as the neurons that project from lateral habenula (LHb) to the VTA and from locus coeruleus (LC) to the VTA. Utilizing retrograding lumafluor fluorescent tracers and electrophysiology techniques, we performed cell type- and circuit-specific measures of neuronal firing rates. Our data show that SCVS significantly increased the firing rate of LHb-VTA circuit neurons in female mice when compared to that of their female controls, an effect that was absent in SCVS-exposed males. Interestingly, SCVS did not induce significant firing alterations in VTA DA neurons and LC-VTA circuit neurons in either female mice or male mice when compared to their stress-naïve controls. Overall, our data show sex differences in the LHb-VTA circuit responses to SCVS, and implicates a potential role of this projection in mediating vulnerability of female mice to stress-induced depression.